2006
DOI: 10.1001/archinte.166.13.1380
|View full text |Cite
|
Sign up to set email alerts
|

Low Testosterone Levels and the Risk of Anemia in Older Men and Women

Abstract: Older men and women with low testosterone levels have a higher risk of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
146
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(159 citation statements)
references
References 41 publications
6
146
2
5
Order By: Relevance
“…Lower testosterone levels are also predictive of anemia in older men, supporting its role as a marker of poorer overall health outcomes. 61,62 In keeping with these observations, over a third of men aged X45 years visiting primary care practices either for general health checks or with specific illnesses had serum total testosterone o10.4 nmol l À1 . 63 Overviews of randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations report improvements in body composition with increased lean body mass and reduced fat mass, but limited benefit in physical capabilities and equivocal improvements in quality of life measures, including general well-being and fatigue.…”
Section: Testosterone General Health and Quality Of Life In Aging Menmentioning
confidence: 61%
“…Lower testosterone levels are also predictive of anemia in older men, supporting its role as a marker of poorer overall health outcomes. 61,62 In keeping with these observations, over a third of men aged X45 years visiting primary care practices either for general health checks or with specific illnesses had serum total testosterone o10.4 nmol l À1 . 63 Overviews of randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations report improvements in body composition with increased lean body mass and reduced fat mass, but limited benefit in physical capabilities and equivocal improvements in quality of life measures, including general well-being and fatigue.…”
Section: Testosterone General Health and Quality Of Life In Aging Menmentioning
confidence: 61%
“…28 Ferrucci and colleagues reported that men in the lowest quartile of total and bioavailable testosterone were more likely to have anemia. 29 Although we did not study serum testosterone lev� els in this study, the lower hemoglobin in the varicocele group could be associated with low testosterone levels.…”
Section: Coban Et Almentioning
confidence: 78%
“…Low T has been related to lower hemoglobin (Hb) levels and a higher risk to develop chronic anemia in older patients [123]. Men under androgen deprivation therapy are more frequently anemic [123].…”
Section: Anemiamentioning
confidence: 99%
“…Men under androgen deprivation therapy are more frequently anemic [123]. Hb levels are related to the severity of androgen deficiency [11] and increase in a linear, dose-dependent manner after TRT [124].…”
Section: Anemiamentioning
confidence: 99%
See 1 more Smart Citation